Carrier‐Free Immobilization of Multi‐Enzyme Complex Facilitates In Vitro Synthetic Enzymatic Biosystem for Biomanufacturing. Issue 6 (27th January 2023) - Liu, Miaomiao; Song, Yunhong; Zhang, Yi‐Heng P. Job; You, Chun
Abstract: A method is developed for carrier‐free immobilization of multi‐enzyme complexes with more than four enzymes by utilization of polypeptide interactions (SpyCatcher‐SpyTag and dockerin‐cohesin) and enzyme component self‐oligomerization. Two pairs of scaffoldins with different arrangements of SpyCatcher‐SpyTag and cohesins are prepared to recruit the four dockerin‐containing cascade enzymes (i. e., alpha‐glucan phosphorylase, phosphoglucomutase, inositol 1‐phosphate synthase, and inositol 1‐phosphatase) that can convert starch into inositol, forming multi‐enzyme complexes. These self‐assembled enzyme complexes show higher initial reaction rates than the four‐enzyme cocktail. Moreover, water‐insoluble self‐assembled multi‐enzyme complexes are observed, being the carrier‐free immobilized multi‐enzyme complex aggregates. These immobilized enzyme complexes can be recycled easily by simple centrifuging followed by resuspension for another round of reaction. Not only can these immobilized enzyme complexes be obtained by mixing the purified enzyme components, but also by the mixing of crude cell extracts. Therefore, the strategy for the carrier‐free immobilization of enzyme complex sheds light on improving the catalytic capability of in vitro synthetic enzymatic biosystems. Abstract : So many enzymes : With a view to potential application of multi‐enzyme complexes in biological multi‐enzyme biocatalysis, a strategy for the carrier‐free immobilization based on protein scaffold is developed by taking the protein‐protein interactions (SpyCatcher‐SpyTag and dockerin‐cohesin) and enzyme oligomerization into account, whereby higher reaction rates and better enzyme recycling are realized.